Performance of analysts' earnings forecasting: Evidence from the Finnish emerging markets 1987 - 2005 - Mikko Kepsu; Hannu Schadewitz; Markku Vieru (The Research Institute of the Finnish Economy (ETLA), 2008)
Financial analysts comprise one important group of information intermediaries between firms and investors (Healy & Palepu, 2001). They have great potential to decrease information asymmetry between firms and investors, resulting in better allocation of capital. Analysts' work is influenced by, among other things, the quality and quantity of information available from the target firms. Furthermore, analysts' incentives could be influenced by the employer's other affairs with the client. Our paper has three purposes: 1) to review the main research literature on analysts' activity and performance, 2) to describe the development of analysts' activity in the period 1987-2005 in a Finnish emerging market, and 3) to analyse the impact of market regulation and market cycles on analysts' performance. Performance is studied in three dimensions: forecasting accuracy, forecast bias, and forecasting efficiency. Analysts' data are based on I/B/E/S. Our analysis shows the rapid development of analysts' activity, both in terms of the number of forecasts and longer forecasting horizons. Overall, the result supports the conclusion that analysts tend to be somewhat pessimistic in their Earnings per share (EPS) forecasts. Furthermore, the corrective actions taken have been somewhat sluggish (delays in EPS revisions). However, the forecasts improved significantly in the close before the actual EPS releases (0-1 month sample). Finally, analysts were not fully taking into account prior EPS development. This further supports the view that analysts underestimate the value of prior earnings change in their current earnings forecasting.
Keywords: 330; analysts' earnings forecasting; emerging markets; Kapitalertrag; Prognose; Finanzanalysten; Aufstrebende Märkte; Finnland